2014
DOI: 10.1016/j.febslet.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Expression of recombinant full‐length plant phytochromes assembled with phytochromobilin in Pichia pastoris

Abstract: a b s t r a c tWe have successfully developed a system to produce full-length plant phytochrome assembled with phytochromobilin in Pichia pastoris by co-expressing apophytochromes and chromophore biosynthetic genes, heme oxygenase (HY1) and phytochromobilin synthase (HY2) from Arabidopsis. Affinity-purified phytochrome proteins from Pichia cells displayed zinc fluorescence indicating chromophore attachment. Spectroscopic analyses showed absorbance maximum peaks identical to in vitro reconstituted phytochromobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…The highest fold induction (∼3.5) was achieved with the combinations of HY1 and PcyA, MTS-mHY1/MTS-mHY2, MTS-mHY1/MTS-PcyA, and MTS-mHmx1/MTS-mHY2 (Figure 5D ). In contrast to published data ( 28 , 29 ), targeting HY1 and PcyA to mitochondria did not gravely boost induction rates compared to cells expressing the two enzymes in the cytoplasm. Still, by combining native HY1 and PcyA we achieved robust expression and doubled the fold induction compared to RL_CT_GI without PCB supply.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The highest fold induction (∼3.5) was achieved with the combinations of HY1 and PcyA, MTS-mHY1/MTS-mHY2, MTS-mHY1/MTS-PcyA, and MTS-mHmx1/MTS-mHY2 (Figure 5D ). In contrast to published data ( 28 , 29 ), targeting HY1 and PcyA to mitochondria did not gravely boost induction rates compared to cells expressing the two enzymes in the cytoplasm. Still, by combining native HY1 and PcyA we achieved robust expression and doubled the fold induction compared to RL_CT_GI without PCB supply.…”
Section: Discussioncontrasting
confidence: 99%
“…The different expression cassettes were genome integrated into the his1-Δ200 locus of RL_CT_GI cells (Figure 5C ). Previous studies in mammalian cells ( 28 ) and Pichia pastoris ( 29 ) revealed optimized chromophore biosynthesis when the two biosynthesis enzymes were targeted to mitochondria, the location of heme biosynthesis in eukaryotes ( 45 ). Accordingly, we deleted the proteins’ native target sequences, if applicable, and replaced them by a yeast-derived mitochondrial targeting sequence (MTS) ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length phytochrome cDNAs of wild-type AsphyA and the AsYVA mutant fused with a 10-amino acid streptavidin affinity-tag at the C terminus were cloned into pPIC3.5K (Invitrogen), and recombinant phytochrome proteins were prepared using the Pichia protein expression system (Invitrogen) and streptavidin affinity chromatography (IBA), as described previously (Kim et al, 2004;Shin et al, 2014Shin et al, , 2016. The QuickChange Site-Directed Mutagenesis System (Stratagene) was used to generate AsYVA with the mutagenic primers shown in Supplemental Table S1.…”
Section: Spectroscopic Analysis Of Recombinant Phytochrome Proteinsmentioning
confidence: 99%
“…For example, although PCB is not naturally produced in nonphotosynthetic species, BV is widely distributed in nature including yeast and mammals. For this reason, biosynthesis of PCB has also been engineered into eukaryotic "chassis" organisms that naturally do not produce these compounds (75)(76)(77)(78). Increased expression of heme oxygenases has been used to enhance the Cyanobacterial photoactivatable adenylyl cyclases synthesis of BV in bacterial and mammalian cells (79,80).…”
Section: Applications Beyond Photosynthetic Speciesmentioning
confidence: 99%